Promotion and strategies of menstrual cup use among healthcare providers: A primer towards a sustainable solution for menstrual health and hygiene management in India - Behera , Surama Manjari; Epari, Venkatarao; Behera, Priyamadhaba; Patro, Binod Kumar (Indian Journal of Community Health, 2024)
Menstrual cups are considered a sustainable solution for menstrual health and hygiene management, as they are cost-effective, environment-friendly, reusable and offer health benefits over traditional menstrual hygiene products such as pads and tampons. However, in lower middle income countries (LMICs), menstrual cup use is limited. Recently, India's current menstrual hygiene program has included menstrual cups as an option for menstrual health and hygiene management. However, the menstrual cup has not been promoted widely in the Indian context. Even if the use of menstrual cups among female healthcare providers in India is minimal, the manuscript identified the crucial challenges in menstrual health and hygiene management, the role of menstrual cups as a solution and the essential strategies to increase menstrual cup use. Programmatic success requires endorsement from healthcare providers as they are trusted sources of information related to healthcare. Good experiences and leading examples from healthcare providers about using menstrual cups is a welcoming step in the path of the dream of a "pad-free country" for India.